Lipase-catalyzed preparation of mono- and diesters of ferulic acid - Sandoval, Georgina; Quintana, Paula G.; Baldessari, Alicia; Ballesteros Olmo, Antonio; Plou Gasca, Francisco José (Biocatalysis and Biotransformation, 2015)
Lipophilic and stable derivatives of ferulic acid are required to improve its efficacy in fatty foods and to optimize its use in cosmetic and pharmaceutical preparations. We report an improved synthesis of ferulic acid monoesters (ethyl ferulate and lauryl ferulate) using immobilized lipase from Candida antarctica B (CALB) in diisopropyl ether (DIPE). Maximum yields were 89% and 85% in 200 h for ethyl and lauryl ferulate, respectively. Ethyl ferulate was further acylated with vinyl esters to form ferulate diesters. 4-Acetoxy-ethyl ferulate was obtained with the immobilized lipase from Alcaligenes sp. (QLG) with 59% yield in 72 h, whereas 4-dodecanoyloxy-ethyl ferulate (a new compound) was synthesized with 52% yield in 72 h using CALB. DIPE was the best solvent for the transesterifications. Finally, the anti-inflammatory activity of the synthesized derivatives was evaluated in vitro; the compounds bearing a dodecyl chain showed improved anti-inflammatory activity compared with short-chain esters. CONACYT (Mexico) I010/ 214/2012-165141, UBA: UBACYT 20020100100304, CONICET: PIP 112-200801-00801/09, and ANPCyT PICT 2011-00595 (Argentina) partially financed this research. Project BIO2013-48779-C4-1-R from Spanish Ministry of Economy and Competitiveness, ENZNUT network (CYTED), and COST action CM1303 on Systems Biocatalysis also supported this work. A.B. is a Research Member of CONICET (Argentina). We thank the Spanish Ministry of Education and Science for a sabbatical grant to G.S. (SB2010-004). Peer Reviewed